1988
DOI: 10.1007/bf00910504
|View full text |Cite
|
Sign up to set email alerts
|

Generalized dysfunction in clinic and nonclinic families: A comparative analysis

Abstract: This study examined the relationship of self-reported marital distress to parental descriptions of emotional or behavioral disturbance of their children using two multidimensional measures of relationship satisfaction and personality functioning in children and adolescents. Data were collected from three independent samples of couples in marital therapy, parents of psychiatrically hospitalized children or adolescents, and nonclinic couples from the general population. Using a split-half cross-validation proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 14 publications
6
35
0
1
Order By: Relevance
“…Camara and Resnick's (1989) study of divorced families found that the degree of cooperation versus noncooperation in the parental role, but not conflict in the spousal role, was predictive of parental warmth and commitment, as well as children's self-esteem and play behavior. Camara and Resnick's (1989) finding has been supported by several studies over the last decade with nondivorced, two-parent families: Coparent relations are a stronger influence on parenting and child adjustment than are other aspects of the couple relationship (Abidin & Brunner, 1995;Bearss & Eyberg, 1998;Jouriles, Murphy, et al, 1991;Snyder, Klein, Gdowski, & Faulstich, 1988). For example, a longitudinal investigation found that observed interparental conflict during family play with a 6-month old infant, but not dyadic marital interaction conflict, predicted attachment security at 3 years (Frosch, Mangelsdorf, & McHale, 2000).…”
Section: Domain Specificity and A Model Of Coparentingsupporting
confidence: 54%
“…Camara and Resnick's (1989) study of divorced families found that the degree of cooperation versus noncooperation in the parental role, but not conflict in the spousal role, was predictive of parental warmth and commitment, as well as children's self-esteem and play behavior. Camara and Resnick's (1989) finding has been supported by several studies over the last decade with nondivorced, two-parent families: Coparent relations are a stronger influence on parenting and child adjustment than are other aspects of the couple relationship (Abidin & Brunner, 1995;Bearss & Eyberg, 1998;Jouriles, Murphy, et al, 1991;Snyder, Klein, Gdowski, & Faulstich, 1988). For example, a longitudinal investigation found that observed interparental conflict during family play with a 6-month old infant, but not dyadic marital interaction conflict, predicted attachment security at 3 years (Frosch, Mangelsdorf, & McHale, 2000).…”
Section: Domain Specificity and A Model Of Coparentingsupporting
confidence: 54%
“…However, Block et al's finding regarding family discord may reflect parent-child conflict rather than marital conflict. Given the negative effects of marital conflict on children (Cummings & Davies, 1994;Jouriles, Murphy, Farris, Smith, Richters, & Waters, 1991;Snyder, Klein, Gdowski, Faulstich, & LaCombe, 1988), the identification of parenting similarity as a risk factor for marital conflict among parents of ADHD children may have important treatment implications. This finding also suggests one possible reason why parents of ADHD children are more likely to divorce than parents of non-ADHD children (Barkley, Fischer, Edelbrock, & Smallish, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies support this idea. Block, Block, and Morrison (1981) found that parental disagreement on child-rearing values predicted adjustment problems in children one to four years later, and Snyder, Klein, Gdowski, Faulstich, and LaCombe (1988) reported that a measure of conflict over child rearing was related to a range of behavior problems in children. Although these studies suggest that child-related conflict is related to children's adjustment, neither study assessed children's exposure to parental conflict or compared this type of conflict with other topics of conflict.…”
Section: Contentmentioning
confidence: 99%